An extended case study on the phenomenology of sequence-space synesthesia - Gould, Cassandra; Froese, Tom; Barrett, Adam B.; Ward, Jamie; Seth, Anil K. (Frontiers in Human Neuroscience, 2014)
Investigation of synaesthesia phenomenology in adults is needed to constrain accounts of developmental trajectories of this trait. We report an extended phenomenological investigation of sequence-space synaesthesia in a single case (AB). We used the Elicitation Interview (EI) method to facilitate repeated exploration of AB's synaesthetic experience. During an EI the subject's attention is selectively guided by the interviewer in order to reveal precise details about the experience. Detailed analysis of the resulting 9 hours of interview transcripts provided a comprehensive description of AB's synaesthetic experience, including several novel observations. For example, we describe a specific spatial reference frame (a “mental room”) in which AB's concurrents occur, and which overlays his perception of the real world (the “physical room”). AB is able to switch his attention voluntarily between this mental room and the physical room of the interview. Exemplifying the EI method, some of our observations were previously unknown even to AB. For example, AB initially reported to experience concurrents following visual presentation, yet we determined that in the majority of cases the concurrent followed an internal verbalisation of the inducer, indicating an auditory component to sequence-space synaesthesia. This finding is congruent with typical rehearsal of inducer sequences during development, implicating cross-modal interactions between auditory and visual systems in the genesis of this synaesthetic form. To our knowledge, this paper describes the first application of an EI to synaesthesia, and the first systematic longitudinal investigation of the first-person experience of synaesthesia since the re-emergence of interest in this topic in the 1980's. These descriptions move beyond rudimentary graphical or spatial representations of the synaesthetic spatial form, thereby providing new targets for neurobehavioral analysis.